Orthorhombic C14 carbon: A novel superhard sp3 carbon allotrope. (January 2020) - Yang, Xigui; Lv, Chaofan; Liu, Shijie; Zang, Jinhao; Qin, Jinxu; Du, Mingrun; Yang, Dongwen; Li, Xing; Liu, Bingbing; Shan, Chong-Xin
Abstract: We establish a novel carbon phase in purely sp 3 -bonded networks with a 14-atom orthorhombic unit cell, termed C14 carbon, by swarm structural searches. This novel carbon phase is dynamically and mechanically stable under ambient conditions. The C14 carbon exhibits a high bulk modulus of 407 GPa and Vickers hardness of 84.3 GPa, which are comparble to those of diamond. Simulated X-ray diffraction pattern is in satisfactory agreement with the previously unresolved diffraction peaks found in detonation soot samples. Interestingly, electronic band structure calculations reveal that the C14 carbon is a semiconductor with a direct band gap of around 4.60 eV. These results establish a novel carbon phase with outstanding mechanical and electronic properties and offer insights for further exploring other carbon allotropes. Graphical abstract: Image 10152191